TEACHING MIND-MAPPING TECHNIQUE TO IMPROVE STUDENTS WRITING DESCRIPTIVE TEXT - Linda Aditiya Kusuma; Lukman Arif Rachman; Arham Mauriyat (IKIP Siliwangi, 2024)
Writing descriptive text is challenging for students nowadays, especially in online learning. Online learning makes students easily bored and tend not to understand what the teacher is explaining. Therefore, an alternative learning technique is needed to maintain student focus and concentration. One technique that teachers can use is the Mind mapping technique. This study aims to determine the effect of Mind mapping technique on students' ability to write descriptive text. The research used quasi-experimental by using One Group Pretest-Posttest as the research design. The subjects of this study were 20 eleventh grade high school students in Cimahi. The researchers used SPSS to analyze the data. Based on the test result, the pretest's mean is 55.80; after the treatment using mind mapping technique, the post-test mean is 75.35, which means that there was a significant improvement when the mind mapping method was being applied. Thus, it can be concluded that mind mapping technique can improve students' writing descriptive text.